Sex differences in impact of cumulative systolic blood pressure from childhood to adulthood on albuminuria in midlife: a 30-year prospective cohort study - Dan Wang; Pu-qing Kou; Yue-yuan Liao; Ke-ke Wang; Yu Yan; Chen Chen; Chao Chu; Yang Wang; Ze-Jiaxin Niu; Qiong Ma; Yue Sun; Jian-jun Mu (BMC, 2023)
Abstract Background and objectives Albuminuria is recognized as being a predictor of cardiovascular and renal disease. We aimed to identify the impact of the long-term burden and trends of systolic blood pressure on albuminuria in midlife, as well as to explore sex differences concerning this relationship. Methods This longitudinal study consisted of 1,683 adults who had been examined 4 or more times for blood pressure starting in childhood, with a follow-up time period of 30 years. The cumulative effect and longitudinal trend of blood pressure were identified by using the area under the curve (AUC) of individual systolic blood pressure measurement with a growth curve random effects model. Results Over 30 years of follow-up, 190 people developed albuminuria, including 53.2% males and 46.8% females (aged 43.39 ± 3.13 years in the latest follow-up). The urine albumin-to-creatinine ratio (uACR) values increased as the total and incremental AUC values increased. Additionally, women had a higher albuminuria incidence in the higher SBP AUC groups than men do (13.3% for men vs. 33.7% for women). Logistic regression showed that the ORs of albuminuria for males and females in the high total AUC group were 1.34 (0.70-2.60) and 2.94 (1.50-5.74), respectively. Similar associations were found in the incremental AUC groups. Conclusions Higher cumulative SBP was correlated with higher uACR levels and a risk of albuminuria in middle age, especially in women. The identification and control of cumulative SBP levels from an early age may assist in reducing the incidences of renal and cardiovascular disease for individuals in later life.